Filsafat Pendidikan Islam dalam Pembentukan Karakter di Kuttab Al-Husnayain Surakarta - Mujiburrohman, Mujiburrohman; Fahriani, Aulia Nurul (TSAQOFAH, 2026)
Although the role of Islamic educational philosophy in shaping students’ character has been widely studied, research that specifically examines its direct application in daily habituation within school environments remains limited. This study aimed to describe how the steps of Islamic educational philosophy are implemented and habituated directly in the process of student character formation. A qualitative approach with an interview-based design was employed, involving three teachers as participants who directly applied habituation practices grounded in Islamic educational philosophy in everyday school activities. Data were collected through in-depth interviews with the teachers and analyzed thematically to reveal patterns of implementation and the meanings they construct regarding student character formation. The interview analysis illustrates the extent to which Islamic educational philosophy is positioned as a normative and practical foundation in behavioral habituation, as well as how teachers understand their role in instilling these values in students. These findings contribute to the development of Islamic educational philosophy theory in student character formation and broaden understanding of the implementation of Islamic philosophical values in educational practice. The study concludes by emphasizing the importance of the consistent application of Islamic educational philosophy by teachers and parents in character-building steps and highlights both theoretical and practical implications for strengthening character education based on Islamic educational philosophy, while also opening opportunities for further exploration in subsequent studies.